An Interdisciplinary Approach to English as a Lingua Franca - Grazzi, Enrico (Status Quaestionis, 2020)
The central theme of this special issue of Status Quaestionis revolves around the controversial nature of English as a lingua franca (ELF), a topic that has gained momentum in language research ever since the process of globalization has turned English into the primary international language in fields as diverse as business, science, technology, education, leisure and tourism.